PROVENCE : Spring/Summer 2021 : Contemporary Art. Biannual. Global. Continuous Crisis. - Pilekjær, Philip (Zürich : PROVENCE, 2021)
Anderson, Mitchell ; Bacon, Francis ; Bader, Darren ; Balogun, Emmanuel ; Blightman, Juliette ; HSH Princess Rita Boncompagni-Ludovisi ; Bonera, Franco ; Bremer, Fabian ; Cahun, Claude ; Calvenzi, Giovanni ; Calvo, Corrado ; Cantor, Lou ; Chacon-Pino, Mateo ; Chetrit, Talia ; Contemporary Art Daily ; Contemporary Art Writing Daily ; Coppetti, Caspar ; Cum, Dom ; Cybulski, Peter ; Dorosheva, Veronika ; Durham, Jimmie ; Duryée-Browner, Elise ; Ellison, Buck ; Fajemisin, Olamiju ; Folly, Gina ; FRZNTE ; Gates, Bill ; Gluhovs, Edgars ; Gygax, Raphael ; Haitz, Samuel ; Hansson, Unn Aurell ; Hecke, Roswitha ; Heger, Swetlana ; Hoffmann, Nelly ; Hollensteiner, Nina ; Irlinger, Julian ; Ismaili, Astrit ; Oliver, Tom ; Jacobson ; Jauss, Marc ; Jones, Mirabelle ; Kvie, Jone ; Lichtenberg, Richard ; Linke, Armin ; Manssur, Alma ; Marman, Mickael ; Meier, Michael ; Minnig, Valentina ; Muslimova, Ebecho ; Nash, Forrest ; Paleari, Paolo ; The Performance Agency ; Petrovich, Dushan ; Philbrick, Inigo ; Pischel, Albrecht ; Pol, Kemara ; Presenhuber, Eva ; Randt, Leif ; Reyes, Federico ; Rico & Michael ; Rinehart, Carter ; Robert, Jimmy ; Rosen, Jeffrey ; Rosengarten, Sarah ; Salomonowitz, Yael ; Satan ; Schachter, Kenny ; Sekula, Allan ; Self, Colin ; Shadow Brand® ; Sulmoni, Mariano ; Valeriani, Claudia ; Warwick, Steven ; Wenzel, Jan ; Wilson, Andrew Norman ; Zavialoff, Alexis ; Zürich Art Memes
boek